2015
DOI: 10.1007/s00500-014-1576-2
|View full text |Cite
|
Sign up to set email alerts
|

Three empirical studies on predicting software maintainability using ensemble methods

Abstract: More accurate prediction of software maintenance effort contributes to better management and control of software maintenance. Several research studies have recently investigated the use of computational intelligence models for software maintainability prediction. The performance of these models, however, may vary from dataset to dataset. Consequently, ensemble methods have become increasingly popular as they take advantage of the capabilities of their constituent computational intelligence models toward a data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 41 publications
1
38
2
Order By: Relevance
“…They found that size metrics were more discriminative that other OO metrics, such as cohesion, coupling and inheritance. Elish et al [5] proposed an empirical study which used ensemble methods on change prediction. They found that ensemble methods can achieve a better performance than individual models.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that size metrics were more discriminative that other OO metrics, such as cohesion, coupling and inheritance. Elish et al [5] proposed an empirical study which used ensemble methods on change prediction. They found that ensemble methods can achieve a better performance than individual models.…”
Section: Related Workmentioning
confidence: 99%
“…The percentage and the number of instances possess a substantial range which can validate the model ability among a wide range. Considering the code metrics, we adopt the typical metrics which are identical with the relevant studies of change prediction [1,5,11,32] as the Table II shows. In detail, five Chidambar and Kemerer metrics [33]: WMC, DIT, NOC, RFC, and LCOM; four Li and Henry metrics [34]: MPC, DAC, NOM, SIZE2; and one traditional lines of code metric (SIZE1) are adopted.…”
Section: B Datasetsmentioning
confidence: 99%
See 3 more Smart Citations